Implementasi Bahan Ajar Bahasa Indonesia Berbasis Virtual Tour untuk Meningkatkan Literasi Digital Siswa SMA - Arip Wira Utama; Fatimah Nur Rohiim; Efrida Qurotul A’yun; Khansa Hafidza; Kundharu Saddhono (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
Merdeka Belajar encourages students to actively utilize technology and get used to digital literacy. Digital literacy includes the ability to use and understand information and communication technology, including the ability to access, evaluate, and use information critically, as well as the ability to communicate and collaborate using technology. The purpose of this research is to describe the condition of teaching materials, explore the need for developing teaching materials, and disseminate Indonesian teaching materials based on virtual tours that can be used in Karaganyar Regency High Schools. This research uses a qualitative descriptive approach. Data collection techniques were carried out by means of active observation, interviews, documentation, and using questionnaires. The results showed that students of SMK Negeri Matesih had an interest in EdLink learning media. The ease of access gives students a high enthusiasm for learning. EdLink learning media provides a positive response, namely: (1) students utilize devices for learning, (2) students can understand the material independently, (3) students are active in asking questions about the material, and (4) students are careful, focused, and effective in utilizing time to do the assessment. From the data obtained, it can be concluded that learning media using EdLink can help students' interest in learning.